KAJIAN ASPEK DEMOGRAFI, SOSIAL, DAN EKONOMI PARTISIPASI TENAGA KERJA WANITA DI PABRIK KAYU LAPIS - Setiasih Irawanti; Mieke Suharti; I M Sulastining (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Plywood industry (wood based industry) is a suitable accupation field for woman labor, where woman can participate in forestry development. The aim of the study is to evaluate participation of woman labor at plywood industry by observing their activities from demographical, social and economical aspects.This study was conducted by collecting data from plywood companies, Provincial Forestry Office, Statistics Office, and interviewing 10 percent of woman and man labors from plywood companies in East Kalimantan province.The results show that about 74 percent of production labor is woman, and most of them work in all sections such as veneer matching and splicing, gluing, pressing, and finishing. About 70 percent of woman labor is unmarried, average age is 24 years with high school education, so they have adequate capacity to work. About 60 percent comes from out of East Kalimantan province. It shows that woman labor at plywood industry has high motivation and mobility to work. Generally, they live in a rent house with minimum condition for their welfare. They usually do not have much time left to participate in social activities commonly organized in surrounding living area.Basic salary of woman labor working for normal shift is Rp. 2,500 and for long shift is Rp. 3,300 per day. It means higher than Minimum Regional Salary determined by goverment office. Woman labor gross income working for normal shift is Rp. 135,000 per month in average or more than Minimum Physical Need of unmarried labor that is only Rp. 86.930,-. While the gross income for those working for long shift is Rp. 242,500 per month or more than Minimum Physical Need for one family consisting of a pair of parents having a child which is only Rp.200,685,-. In conclusion, woman labor income can give a